2018
DOI: 10.1038/s41598-018-22255-3
|View full text |Cite
|
Sign up to set email alerts
|

Central s-resistin deficiency ameliorates hypothalamic inflammation and increases whole body insulin sensitivity

Abstract: S-resistin, a non-secretable resistin isoform, acts as an intracrine factor that regulates adipocyte maduration, inflammatory and insulin response in 3T3-L1 cells. However, its intracellular function in vivo is still unknown. In this study, we analyze the central role of s-resistin, decreasing its hypothalamic expression using an intracerebroventricular injection of lentiviral RNAi. The data present herein support an improvement in the hypothalamic leptin and insulin signaling pathway upon s-resistin downregul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Resistin was found to cause insulin resistance 14 , 15 , 16 , 17 . It can completely reverse insulin resistance by normalizing plasma resistin level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resistin was found to cause insulin resistance 14 , 15 , 16 , 17 . It can completely reverse insulin resistance by normalizing plasma resistin level.…”
Section: Introductionmentioning
confidence: 99%
“…It can completely reverse insulin resistance by normalizing plasma resistin level. Subsequently, a large number of studies show that resistin plays an important role in the occurrence and development of a variety of inflammatory diseases 15 , 16 . It has been suggested that resistin may be a molecular link between inflammation, metabolism, and vascular dysfunction 18 , leading to the risk of MetS, type 2 diabetes, and cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…The destruction of the neurons of the arcuate nucleus significantly diminishes the expression of resistin in the pituitary gland [65]. In the hypothalamus, a shorter form of resistin (s-resistin), which is the intracellular form and is not secreted, was found [67]. The inhibition of s-resistin synthesis resulted in an increase in the activity of leptin signalling pathways and an insulin pathway in the rat hypothalamus.…”
Section: Resistinmentioning
confidence: 99%